Effect of temperature and shear rate on rheological behavior of contaminated marine hydraulic fluid - W.B., Wan Nik; F., Zulkifli; M.M., Rahman; E.G., Goh; N., Aqilah (2018)
Ship uses various types of oil either for fuel, power or lubricity. For lubricity purposes, various types of lubricants are used on board. Since the marine machineries are working in aquatic environment, the lubricating fluid working in each machine is prone to water contamination. In this work, effects temperature, shear rate and contaminant level on rheological behaviors of water contaminated hydraulic fluid were examined. Power law model and Cross-Careau models were applied to the experimental data. The findings show that the contaminated fluid shows some non-Newtonian behavior.